The end of moderate inflation in three transition economies? - Josef C. Brada; Ali M. Kutan (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 1999)
This paper examines the ending of moderate rates of inflation in three transition economies, the Czech Republic, Hungary and Poland at the end of 1998. We argue that the institutions for the conduct of monetary policy in these countries were relatively weak and that monetary policy was unsupported by fiscal policy and hampered by multiple objectives. Using a VAR model of inflation, we show that, under a variety of assumptions, foreign prices and the persistence of inflation are the key determinants of inflation in these countries. From this finding we conclude that the end of moderate inflation in the Czech Republic, Hungary and Poland was largely due to the decline in import prices in the second half of 1998, and thus it may be a temporary phenomenon.
Keywords: P2; E5; 330; Monetary and fiscal Policy; transition economies; moderate inflation; inflation targeting